The impact of Porphyromonas gingivalis and its virulence in cardiovascular diseases - Parra Pérez, Anna Sofía; Plaza, Diana del Mar; Gómez Gonzalez, Sofia; Moreno Correa, Sandra (Revista Estomatología, 2025)
Aim: To describe the pathogenic mechanisms used by P. gingivalis to migrate to the heart and infect the heart valves.Materials and methods: A systematic search of the information is carried out from the PRISMA Declaration to obtain sources of information, the MeSH health descriptors "Porphyromonas gingivalis", "Infection mechanisms" and "Valvular heart disease" are |obtained, which were combined through the boolean “AND” connector.Results: Two types of searches were carried out, in which a total of 61 articles were analyzed, where four studies related to the chosen theme were found, including two original scientific research articles and two observational articles; a conventional PCR method was used to detect P. gingivalis in all the articles.Conclusion: Several studies carried out in patients with periodontal disease with or without the presence of concomitant valvular disease have managed to isolate the periodontopathogen in heart valves, although its proportion is minimal compared to other pathogens, however, the pathogenic mechanism by which P. gingivalis infects heart valves has not been identified, and research is needed to obtain accurate information on the relationship between infection caused by P. gingivalis and valve disease.